2022
DOI: 10.1101/gad.349489.122
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation and chromatin architecture maintenance are decoupled functions at the Sox2 locus

Abstract: How distal regulatory elements control gene transcription and chromatin topology is not clearly defined, yet these processes are closely linked in lineage specification during development. Through allele-specific genome editing and chromatin interaction analyses of the Sox2 locus in mouse embryonic stem cells, we found a striking disconnection between transcriptional control and chromatin architecture. We traced nearly all Sox2 transcriptional activation to a small number of key transcription factor binding si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 93 publications
6
35
0
Order By: Relevance
“…While an attractive model, RNA polymerase II is absent from the inactive Bcl6 gene in ESCs, where a relatively strong but somewhat broader TAD border is nevertheless maintained at the promoter, so other mechanisms must also contribute to architectural maintenance at this locus ( Fig 3B ). Conserved CTCF binding at the promoter would be expected to be such a mechanism, although homozygous deletion of the major binding site had mild effects on locus architecture ( Fig S5 ), in line with other studies suggesting that TADs are built up cooperatively from multiple elements (Despang et al, 2019; Rodríguez-Carballo et al, 2017; Taylor et al, 2022).…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…While an attractive model, RNA polymerase II is absent from the inactive Bcl6 gene in ESCs, where a relatively strong but somewhat broader TAD border is nevertheless maintained at the promoter, so other mechanisms must also contribute to architectural maintenance at this locus ( Fig 3B ). Conserved CTCF binding at the promoter would be expected to be such a mechanism, although homozygous deletion of the major binding site had mild effects on locus architecture ( Fig S5 ), in line with other studies suggesting that TADs are built up cooperatively from multiple elements (Despang et al, 2019; Rodríguez-Carballo et al, 2017; Taylor et al, 2022).…”
Section: Resultssupporting
confidence: 86%
“…The latter are dependent on underlying gene activity and epigenetic state so are developmentally plastic, as observed (Dixon et al, 2015;Bonev et al, 2017), whereas loop extrusion barriers could be genetically coded, such as by CTCF binding sites, so in this model TADs would not be expected to change significantly across cell type. However, CTCF occupancy is not identical in all cell types and in any case does not account for all TADs (Nora et al, 2017;Taylor et al, 2022). Recent studies have shown that non-encoded features as diverse as MCM complex binding (minichromosome maintenance; most famous for replication origin licensing) and DNA double-strand breaks can also be barriers to loop extrusion (Arnould et al, 2021;Dequeker et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations